Oral community health worker-led interventions in households with average levels of psychosocial factors - Lee, Helen H.; Avenetti, David; Edomwande, Yuwa; Sundararajan, Vyshiali; Cui, Liyong; Berbaum, Michael; Nordgren, Rachel; Sandoval, Anna; Martin, Molly A. (Frontiers in Oral Health, 2022)
Introduction Household-level psychosocial stress levels have been linked to child tooth brushing behaviors. Community health worker (CHW) interventions that target psychosocial factors in high-risk communities have been associated with changes in health behaviors. Aim Observe changes in psychosocial factors over time and an association between psychosocial factors and CHW intervention dose amongst urban Chicago families. Patients and methods Participants (N = 420 families) were recruited from 10 community clinics and 10 Women, Infants, or Children (WIC) centers in Cook County, Illinois to participate in a clinical trial. Research staff collected participant-reported psychosocial factors (family functioning and caregiver reports of depression, anxiety, support, and social functioning) and characteristics of CHW-led oral health intervention visits (number, content, child engagement) at 0, 6, and 12 months. CHWs recorded field observations after home visits on household environment, social circumstances, stressors, and supports. Results Participants across the cohort reported levels of psychosocial factors consistent with average levels for the general population for nearly all measures. Psychosocial factors did not vary over time. Social functioning was the only measure reported at low levels [32.0 (6.9); 32.1 (6.7); 32.7 (6.9); mean = 50 (standard deviation)] at 0, 6, and 12 months. We did not observe a meaningful difference in social functioning scores over time by exposure to CHW-led intervention visits (control arm, 0, 1, 2, 3, and 4 visits). Field observations made by CHWs described a range of psychosocial stress related to poverty, language barriers, and immigration status. Conclusion The unexpectedly average and unchanging psychosocial factors over time, in the context of field observations of stress related to poverty, lack of support, immigration status, and language barriers, suggests that our study did not adequately capture the social determinants of health related to oral health behaviors or that measurement biases precluded accurate assessment. Future studies will assess psychosocial factors using a variety of instruments in an attempt to better measure psychosocial factors including social support, depression, anxiety, functioning, trauma and resilience within our urban population. We will also look at neighborhood-level factors of community distress and resilience to better apply the social ecologic model to child oral health behaviors.